Persepsi Publik terhadap Penyandang Disabilitas di Kota Kupang Nusa Tenggara Timur - Habaora, Fellyanus; Riwukore, Jefirstson Richset; Susanto, Yohanes; Manafe, Hilda (Jurnal Penelitian Kesejahteraan Sosial, 2019)
Research on public perceptions towards persons with disabilities with case research in Kota Kupang has been carried out for 7 months, starting from June-December 2018. Determination of respondents' samples using a purposive sampling technique. Based on this technique, the respondents in this research were 51 people. The types of data used are primary and secondary data. Data obtained were then analyzed descriptively (qualitative and quantitative) based on frequency distribution tables and measurements using a Likert scale. The results showed that the public's perception of persons with disabilities in Kota Kupang, namely: (1) someone who has a disability would certainly experience biomedical, social and biopsychosocial discrimination and stereotypes; (2) the perception of the Kota Kupang Government paying attention to persons with disabilities in the disagree category because the public considers that the facilities, policies, and services by the government have not been disability-friendly; (3) public perceptions of the existence of persons with disabilities need to protect shows in the strongly agree category if the interests of disability are very urgent, disability strengthening is very important, disability protection and inclusive friendly policies are needed as the government's commitment to carry out protection and fulfillment of human rights in Kota Kupang.